Identification of a Novel Salt Tolerance-Related Locus in Wild Soybean (Glycine soja Sieb. & Zucc.) - Guo, Xiaoyang; Jiang, Jinghan; Liu, Ying; Yu, Lili; Chang, Ruzhen; Guan, Rongxia; Qiu, Lijuan (Frontiers in Plant Science, 2021)
Salinity is an important abiotic stress factor that affects growth and yield of soybean. NY36-87 is a wild soybean germplasm with high salt tolerance. In this study, two F2:3 mapping populations derived from NY36-87 and two salt-sensitive soybean cultivars, Zhonghuang39 and Peking, were used to map salt tolerance-related genes. The two populations segregated as 1 (tolerant):2 (heterozygous):1 (sensitive), indicating a Mendelian segregation model. Using simple sequence repeat (SSR) markers together with the bulked segregant analysis (BSA) mapping strategy, we mapped a salt tolerance locus on chromosome 3 in F2:3 population Zhonghuang39 × NY36-87 to a 98-kb interval, in which the known gene GmSALT3 co-segregated with the salt tolerance locus. In the F2:3 population of Peking × NY36-87, the dominant salt tolerance-associated gene was detected and mapped on Chromosome 18. We named this gene GmSALT18 and fine mapped it to a 241-kb region. Time course analysis and a grafting experiment confirmed that Peking accumulated more Na+ in the shoot via a root-based mechanism. These findings reveal that the tolerant wild soybean line NY36-87 contains salt tolerance-related genes GmSALT3 and GmSALT18, providing genetic material and a novel locus for breeding salt-tolerant soybean.